KEPEMIMPINAN KEPALA MADRASAH DALAM PENERAPAN MANAJEMEN BERBASIS SEKOLAH PADA MTSN LAWANG MANDAHILING - Nurlaili Nurlaili (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
Leadership of Head Madrasah In Implementation Management Based of in MTsN Lawang Mandahiling. As a result of this research include: The leadership style of the head master of school is style democracy. The high school governmental organizations Lawang Mandahiling implement school - based management as well. The supporting factors in the application of school - based management which are as follows: Many support and participation of the community and parents of pupils and the local government. To this school vision, mission that clear . The headmaster had a democratic leadership school committee has its job well. If appropriate school and harmonious interaction between entering and leaving. Factors obstacles in the application of school - based management which are as follows: There are some parents of poor students . Knows some materials that teachers vary scientific qualifications . Few facilities supporting the education process with that there is the work of the school and the community and parents of pupils and the local government.Kata Kunci: kepemimpinan, manajemen berbasis sekolah